Digital Transformation in the Educational Process for University Students Case Study: Sociology Department Students at Lattakia University (Damascus University Journal of arts and humanities sciences, 2026)
The aim of the research was to study the digital transformation in the educational process. To achieve this goal, the descriptive analytical approach was used, the social survey method by sample, using a scale prepared by the researcher, and distributed to a sample of students of the Department of Sociology at the University of Lattakia, which was drawn by a simple random method (lottery) The size of this sample was 290 male and female students. After collecting and transcribing the data using the SPSS program and using appropriate statistical methods, a set of results was reached, the most important of which was that the level of university use of digital tools in the Department of Sociology at the University of Lattakia falls within the "average" range and that it is still confined to some limited frameworks, and does not reflect a real shift towards comprehensive digitization of educational and administrative functions within the department. As for students' reliance on digital tools, it was high, especially in terms of obtaining information, using them to complete projects and research, and obtaining scientific references. The results also showed the existence of many challenges facing university students in this area, the most important of which were weak internet networks, difficulty in regularly accessing educational content electronically, and weak infrastructure equipment in universities. As for the differences between students' reliance on digital tools in the educational process, the results did not show any differences with regard to gender and place of residence, but rather showed the existence of differences only with regard to the year of study in favor of the higher years. At the end of the research, a set of scientific proposals were presented that may contribute to raising the level of universities' reliance on rapid technological developments, incorporating them into the educational process, and exploiting them to raise the level of universities as much as possible and keep pace with global development.
Keywords: Digital Transformation; Technology; Digital Learning; University Youth; University Education